Carter's conversion the hardening of American defense policy - Auten, Brian J., 1969- (University of Missouri Press, 2008)
"Examining Carter's dramatic shift from advocating defense budget cuts early in his administration to supporting development of the MX missile and modernization of NATO's Long-Range Theater Nuclear Force by the end of his presidency, the author argues, counter to common interpretations, that the shift was a "self-correcting" policy change in response to the prevailing international military environment"--Provided by publisher.